Resolving Land Disputes Through Land Offices and Customary Institutions: Perspectives from National and Customary Law in Aceh - Darmawan, Darmawan; Jauhari, Iman; Suhaimi, Suhaimi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Land disputes, which frequently arise, require comprehensive policies and integrated solutions for effective resolution. At the national level, the government has issued technical regulations through Ministerial Regulations. In Aceh, however, land dispute resolution also falls under the jurisdiction of regional laws, including the Aceh Governance Law and Qanun, which reflect customary practices. This study employs an empirical legal research method, using a socio-legal approach to analyze how law operates within the society. Data were collected through in-depth interviews and document analysis. Respondents included officials from the Land Office, members of the Aceh Customary Council (MAA), customary leaders, academics, and local community members. Documents reviewed consisted of legal regulations, case reports, journal articles, and academic texts related to land disputes. The study finds that the Land Office resolves land disputes through a multi-step process: Case Study, Preliminary Assessment, Investigation, Presentation of Findings, Coordination Meeting, Final Assessment, and Case Resolution. However, traditional leaders and institutions such as the Aceh Customary Council have not been involved in this process, despite their official role in supporting governance, development, community affairs, and social conflict resolution. Currently, the Land Office and customary institutions operate independently, each following its own procedures. The study argues that a more integrated approach between the two entities could enhance the effectiveness of land dispute resolution. Such collaboration would strengthen the legitimacy and public trust in both institutions. Furthermore, customary law has demonstrated its capacity to resolve societal conflicts, including land disputes, thereby underscoring the value of incorporating traditional mechanisms into formal legal processes.